2014
DOI: 10.1507/endocrj.ej13-0305
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 inhibition with alogliptin on top of angiotensin II type 1 receptor blockade ameliorates albuminuria <i>via</i> up-regulation of SDF-1α in type 2 diabetic patients with incipient nephropathy

Abstract: DipeptiDyl peptiDase-4 (DPP-4) inhibitor is a new class of anti-diabetic drug which enhances circulating levels of a gut incretin hormone, glucagon-like peptide-1 (GLP-1), by inhibiting the degradation of GLP-1 [1]. GLP-1 stimulates insulin secretion from pancreatic β-cells in a blood glucose-dependent manner and suppresses glucagon release from pancreatic abstract. Dipeptidyl peptidase-4 (DPP-4) inhibitor is a new class of anti-diabetic drug which exerts its glucose-lowering action by suppressing the degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 37 publications
1
77
2
2
Order By: Relevance
“…To the authors' knowledge, this is the first study that evaluates the effect of a DPP-4 inhibitor on renal vanin-1 in experimental DN. The antioxidant properties attributed to DPP-4 inhibitors were depicted in experimental diabetic models [36,52] and T2D patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, this is the first study that evaluates the effect of a DPP-4 inhibitor on renal vanin-1 in experimental DN. The antioxidant properties attributed to DPP-4 inhibitors were depicted in experimental diabetic models [36,52] and T2D patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…As the first approved DPP-IV inhibitor to reach the market, sitagliptin can reduce the inactivation of GLP-1 and increase active GLP-1 levels in vivo by selectively inhibiting DPP-IV to effectively control BG [35]. Fujita et al [36] recently found that DPP-IV inhibitors can activate cAMP/PKA signaling channels in patients with early type-2 DN, reducing oxidative stress, inhibiting apoptosis, improving proteinuria, and protecting the kidney by upregulating GLP-1. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, type 2 diabetic patients, treated with saxagliptin and followed for a median of 2.1 years, were significantly more likely than patients treated with placebo, to have a lower UACR (Scirica et al 2013). Moreover, Fujita and coworkers (Fujita et al 2014b) performed a cross-over study to investigate the effects of sitagliptin and alogliptin in twelve patients, with diabetic nephropathy, taking ARBs. The treatment regimen consists of three periods; sitagliptin for 4 weeks, alogliptin for 4 weeks and again sitagliptin for 4 weeks.…”
Section: Clinical Data On Dpp-4 Inhibitors In Diabetic Nephropathymentioning
confidence: 99%